1991
DOI: 10.1017/s0007123400006189
|View full text |Cite
|
Sign up to set email alerts
|

Political and Economic Explanations for Unemployment: A Cross-National and Long-Term Analysis

Abstract: This article shows that the widely accepted supply shock and real wage gap explanation of increases in unemployment rates since 1973 has only limited empirical support. The causal factors behind unemployment are best understood by focusing on conflicts of interest in Western democracies, on the distribution of power resources between major interest groups and on strategies of conflict. Given economic constraints, from this perspective unemployment appears as the labour market expression of distributive conflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…7 In order to minimise distortions arising from cyclical and seasonal fluctuations and possible measurement errors, as well as to reflect appropriately the general level of unemployment rates, we analyse averages from 2003 to 2006. Aside from a general tendency towards analysing regional politics, unemployment, too, is more and more understood as a regional structural problem (Eurostat Jahrbuch, 2007; Huber, 2008; Keller, 1999, p. 341; Korpi, 1991, p. 325; Piazolo, 2002; Saint‐Paul, 2002). Following previous studies we proceed on the assumption that the European regions can be considered as separate labour markets due to linguistic and cultural barriers (Filippini, 1998; Nickell, 1997; Van Dijk et al ., 1989; Windzio, 2004).…”
Section: Method Data and Operationalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In order to minimise distortions arising from cyclical and seasonal fluctuations and possible measurement errors, as well as to reflect appropriately the general level of unemployment rates, we analyse averages from 2003 to 2006. Aside from a general tendency towards analysing regional politics, unemployment, too, is more and more understood as a regional structural problem (Eurostat Jahrbuch, 2007; Huber, 2008; Keller, 1999, p. 341; Korpi, 1991, p. 325; Piazolo, 2002; Saint‐Paul, 2002). Following previous studies we proceed on the assumption that the European regions can be considered as separate labour markets due to linguistic and cultural barriers (Filippini, 1998; Nickell, 1997; Van Dijk et al ., 1989; Windzio, 2004).…”
Section: Method Data and Operationalisationmentioning
confidence: 99%
“…The same logic applies to labour force growth which enhances labour supply and, at the same time, the level of unemployment (Armingeon, 2003; Bean, 1994). Furthermore, the better off an economy, that is, the better the economic growth and labour productivity, the lower the level of unemployment (Basile and DeBenedictis, 2008; Bean, 1994; Freitag, 2000; Korpi, 1991; Schmidt, 1987; Suedekum et al ., 2006). The diversity of the industry mix also contributes to lower levels of unemployment (Elhorst, 2003; Parnisari, 2003).…”
Section: Method Data and Operationalisationmentioning
confidence: 99%
“…It is also quite possible, however, that the distribution of income has sizeable effects on only certain aspects of economic performance. Recent research suggests, for instance, that variation in unemployment rates is largely determined by government policy choices not easily captured in quantitative form (Therborn 1986;Korpi 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This part of Olson's argument is unconvincing. There is little or no empirical basis for the assumption that rent-seeking interest groups are less numerous and powerful in nations suffering disruptions than in those characterized by long periods of stability (Cameron 1988 A number of studies have found party ideology, as represented by the partisan complexion of government, to affect cross-national variation in economic performance, especially unemployment and inflation (Hibbs 1977;Alt 1985;Korpi 1991;Suzuki 1993;Whiteley 1983). Rather than include this variable, I have chosen to use direct indicators of government 9.…”
Section: See Mahlermentioning
confidence: 99%
“…Whether studying individual social programs, such as pensions, sickness benefits, or labor market policies (Myles, 1984;Korpi, 1989Korpi, , 1991, or more broadly 'welfare states' (Stephens, 1979;Korpi, 1983;Esping-Andersen, 1990;Hicks, 2000), the impact of the political strength of the left is quite robust. Whether studying individual social programs, such as pensions, sickness benefits, or labor market policies (Myles, 1984;Korpi, 1989Korpi, , 1991, or more broadly 'welfare states' (Stephens, 1979;Korpi, 1983;Esping-Andersen, 1990;Hicks, 2000), the impact of the political strength of the left is quite robust.…”
Section: The 'Politics Matter' Thesismentioning
confidence: 99%